Evaluation of Technology Use in Supporting the Teaching and Learning of Christian Religious Education at Arastamar Theological Seminary Wamena - Ballen, Zofar Wilson; Rasinus, Rasinus; Rukua', Ivo Sastri; Karlau, Sensius Amon; Tasak, Edie Rante (Yayasan Banu Haji Samsudin, 2025)
This study is motivated by the question of how effectively technology can support the teaching and learning of Christian Religious Education at Arastamar Theological Seminary Wamena, an institution operating within the geographical and digital infrastructure limitations of Papua. The author argues that technology holds strategic potential to expand access, enhance interactivity, and enrich the learning experience of theology students; however, its integration must be sensitive to the social, cultural, and spiritual context of Papuan society. Theories of technology-based learning and Christian pedagogy suggest that technology can serve as an effective tool when critically and contextually adapted. This research employs a qualitative method involving interviews, observations, and document analysis to evaluate the practice of technology use at Arastamar Theological Seminary Wamena. The findings indicate that digital technology has been integrated into the curriculum and has positively influenced the quality of learning, though significant challenges remain—particularly in terms of infrastructure, digital literacy, and resistance among some lecturers and students. The study concludes that technology can strengthen the process of Christian religious education when managed wisely and contextually, and it highlights the need for continuous policy development and training for Christian educators in remote regions.